PENGARUH PERHATIAN ORANG TUA DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA PESERTA DIDIK KELAS V SEKOLAH DASAR - Putriayu, Ninda; Sofia, Ari; Nuraini, Siti; Erni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem in this study was the low learning outcomes of fifth-grade elementary school students in Pancasila Education. This study aimed to: (1) determine the effect of parental attention on students’ learning outcomes in Pancasila Education, (2) determine the effect of learning motivation on students’ learning outcomes in Pancasila Education, and (3) determine the combined effect of parental attention and learning motivation on students’ learning outcomes in Pancasila Education. The method used in this study was multiple regression with an ex post facto research design. The population of this study consisted of 151 students, and the sample was determined using proportionate stratified random sampling, resulting in a sample of 109 students. Data collection techniques used non-test methods in the form of questionnaires and documentation. The data collection instruments were parental attention and learning motivation questionnaires using a Likert scale, which had passed validity and reliability tests. Data analysis was conducted using multiple regression analysis. The results of the study showed that: (1) there was an effect of parental attention on students’ learning outcomes in Pancasila Education, (2) there was an effect of learning motivation on students’ learning outcomes in Pancasila Education, and (3) there was a combined effect of parental attention and learning motivation on students’ learning outcomes in Pancasila Education.